Copolymerization of propylene oxide and carbon dioxide - Narang S.; Mehta R.; Upadhyay S.N. (My University, 2025)
The alternating copolymerization of carbon dioxide and epoxides to give polycarbonates and cyclic carbonates has attracted the attention of researchers since it fixes CO2, a green house gas, chemically. This review makes an attempt to present a critical assessment of the available information particularly on copolymerization of propylene oxide and CO2 and thereby indicates the areas and gaps where further work is required. The efficacy of various inorganic, organometallic and ligand metal complexes has been thoroughly analyzed. © 2015 Bentham Science Publishers.